A cognitive and corpus-based study of the connotative potential of the adjectives czerwony ‘red’ and czarny ‘black’ in modern Polish political discourse - Martyna Awier (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The paper discusses metaphorical and metonymic extensions of the adjectives czerwony ‘red’ and czarny ‘black’. The connotative potential of red and black colour collocations is analyzed and discussed. Red and black collocations were excerpted from the two largest corpora, i.e. NKJP and MoncoPL. All colour citations are analysed in the framework of discourse analysis and conceptual metaphor and metonymy. The analysis indicates that extralinguistic factors (i.e. social, political and historical events) motivate the emergence of red and black colour collocations in modern Polish discourse.